An N-sulfanylethylanilide-based traceable linker for enrichment and selective labelling of target proteins. Issue 42 (5th May 2016) - Morisaki, Takuya; Denda, Masaya; Yamamoto, Jun; Tsuji, Daisuke; Inokuma, Tsubasa; Itoh, Kohji; Shigenaga, Akira; Otaka, Akira
Abstract : An N -sulfanylethylanilide (SEAlide)-based traceable linker has been developed for the identification of the target proteins of bioactive compounds. Abstract : An N -sulfanylethylanilide-based traceable linker, developed to facilitate identification of target proteins of bioactive compounds, was introduced into an alkynylated target protein. Subsequent adsorption onto streptavidin beads allowed it to be treated with a cysteine–fluorophore conjugate in the presence of phosphate. This induced the N – S acyl transfer reaction of the N -sulfanylethylanilide unit. The subsequent native chemical ligation of the fluorophore resulted in cleavage of the linker for target elution and fluorescence labelling of the target, allowing it to be distinguished from non-target proteins.